Association of Serum Ceruloplasmin Level with Parkinson’s’s Disease (Bangladesh Journal of Neuroscience, 2018)
Background: Parkinson’s disease, though a common neurodegenerative disease, is still elusive regarding its pathobiology. Neuronal degeneration in the midbrain substantia nigra by excess oxidative stress may play a role. As ceruloplasmin (Cp), a plasma protein is important to maintain intracellular iron homeostasis and reduce cellular oxidative stress, decreased serum Cp level may be an important factor in the pathogenesis of Parkinson’s disease.Methods: This case-control study was conducted in the department of Neurology, BSMMU. Forty-five Parkinson’s disease patients and equal number of controls were selected. Serum ceruloplasmin level was measured in the department of Biochemistry and Molecular Biology, BSMMU.Results: Mean serum Cp level was significantly lower (p-value